Job Satisfaction Analysis in Rural China: A Qualitative Study of Doctors in a Township Hospital - Qiwei Chen; Lan Yang; Qiming Feng; Scott S. Tighe (Scientifica)
Background. Township hospitals in China provide rural communities with basic but much needed critical health care services. The doctors working in these hospitals often feel unsatisfied when considering their work schedules and financial rewards. Method. To explore job satisfaction of health workers in a township hospital, a qualitative study was conducted of 39 doctors from five township hospitals in Guangxi Zhuang Autonomous Region. The goal was to understand the level of job satisfaction of doctors and to make recommendations for improvements. Results. About 75% (28/39) of the doctors expressed negative attitudes related to their work conditions. Slightly more than half (22/39) mentioned they should receive greater compensation for their work and more than one were seriously considering other options. Many participants (35/39) showed their satisfaction about the achievement of serving as a doctor. Conclusion. Their main concerns related to job satisfaction included working conditions, financial rewards, and the doctor’s relationships with patients. Increasing the incomes and fringe benefits of healthcare workers, improving their work conditions, and providing training and continuing education opportunities would help rural clinics retain doctors and eliminate the current unsatisfactory conditions. The findings also highlight the need for the government to increase financial support of township hospitals.